The role of TLR-3 in the course and outcomes of rotavirus infection in infants - S. G. Gorbunov; L. N. Mazankova; A. N. Os'kin (LLC "Diagnostics and Vaccines", 2022)
It was found that the clinical picture of rotavirus infection in infants with an initially low number of immunocompetent cells expressing TLR-3 does not differ significantly from that of patients with an initially large number of cells expressing TLR-3. When analyzing the treatment, it turned out that antibacterial therapy due to the activation of bacterial microflora was used only in children with an initially low number of immunocompetent cells expressing TLR-3. In the same group of patients, the development of atopic dermatitis and food allergies was noted during catamnestic observation for 6-12 months after rotavirus infection.